MODERN TENDENCIES AND PROBLEMS OF RURAL POPULATION DYNAMICS OF RA (Proceedings of the YSU C: Geological and Geographical Sciences, 2015)
Political, economic and social-cultural changes in RA during the last 20 years have caused significant changes in population number, structure, distribution, as well as demographic situation. They are more obvious in marzes and regions of RA, particularly, in rural settlements. In the article the population dynamics of rural population of RA, the features of regional changes and problems in 2005–2013 are analyzed.
Keywords: demographic situation; rural settlement; social-cultural changes